CLINICAL SIGNIFICANCE OF PLASMA MIR-21, MIR-141, MIR-29C, AND MIR-BART7 IN PATIENTS WITH LOCALLY ADVANCED NASOPHARYNGEAL CANCER AND THEIR ALTERATIONS AFTER CHEMORADIATION THERAPY - Cita Herawati (TALENTA PUBLISHER, 2019)
Introduction: Plasma microRNAs (miRNAs) are biological markers that have been extensively studied in cancer, including nasopharyngeal cancer (NPC). The clinical significance of miRNA in NPC patients in Indonesia has never been studied. Objective: This study was aimed to know the expression of plasma miRNAs in NPC patients (miR-21, miR-29c, miR-141dan miR-BART7) and their relationship with clinicopathological characteristics and treatment response. Method: This was a cohort, longitudinal study among locally advanced NPC patients (stage IIB-IVB) in Dharmais Cancer Hospital, Jakarta. miRNA expression was assayed using quantitative real-time polymerase chain reaction (qRT-PCR) technique. Four miRNAs were evaluated, i.e., miR-21, miR-29c, miR-141, and EBV-miR-BART7. The results were normalized against a reference gene, miR-16. Result: A total of 52 patients and 10 normal subjects were enrolled in this study; 17 of them completed treatment. Patients’ mean age was 45.1+12.53 (14-68) years. The ratio between men and women was 3:1. MiR-21 and miR-29c could be detected in all subjects; miR-141 was detected in 22 (42.3%) and EBV-miR-BART7 in 26 (50%) subjects. There was no significant difference between miR-21 or miR-29c expression between before and after therapy. However, miR-21 expressions tend to decrease in a patient with complete response (CR) (4.13+3.65 vs. 2.74+3.23; p=0.650) and tend to increase in patients with partial response (PR) (3.00+5.86 vs. 8.77+8.43; p=0.465). There was no difference of miR-29c expression between CR and PR patients. Conclusion: Our study shows that not all miRNA can be detected in the plasma of NPC patients. Levels of miRNA expressions in these locally advanced patients are similar. Expression of miR-21 is potentially used as a biomarker of evaluating treatment response in NPC patients.